Placement for Ministry of Theological Schools Graduates of the Tobolsk Consistory in the Second Half of the 18th - Early 20th Centuries (according to the Materials of the Archive of the Tobolsk Spiritual Consistory) - A. V. Spichak (Научный диалог)
The relevance of the problem under discussion is due to the growing importance of the Russian Orthodox Church in the development of the spiritual culture of modern society, the need to understand its centuries-old historical experience, including the placement for ministry of graduates. The issues of employment of graduates from various educational institutions to places of ministry are considered on the example of the Tobolsk diocese - one of the largest in the Russian Empire. On the basis of a considerable number of sources, the task is to analyze the peculiarities of records management related to the petitions of the students of theological seminaries and religious schools about the placement of ministry in the church of the Tobolsk diocese. The analysis of archival materials testifies to the presence in the second half of the 18th - early 20th centuries of an established procedure for appointing graduates from various educational institutions to various positions in the churches of the Tobolsk diocese. The stages of this process are characterized. The study of the documents of the Tobolsk spiritual consistory allows us to conclude that the paperwork on this issue took from several days to two years. It is reported that the bishop usually made the decision on the day the petition was filed, but the process of applying for a service could be delayed. Most likely, graduates of religious schools who sought places of clergy received the desired position, as they had simplified requirements.